Novel sensitive high-performance liquid chromatographic method for assay of coumarin 7-hydroxylation - Soucek, P (Journal of chromatography. B, Biomedical sciences and applications, 1999)
In this paper, a novel HPLC-based method with fluorometric detection of coumarin 7-hydroxylase is presented. The described method provides a time-effective, more sensitive and specific alternative to the previously used spectrofluorometric assay. Using the developed method, metabolism of coumarin in 11 samples of human liver microsomes was evaluated and 1790+/-690 pmol/min/nmol cytochrome P450 (CYP) activity was found. Kinetic parameters and linearity of coumarin 7-hydroxylation were studied in a reconstituted system consisting of recombinant CYP2A6 expressed in Escherichia coli, rat NADPH-CYP reductase and usual components. It was found that a 3.5 to 30 min time of incubation is suitable for estimation of coumarin 7-hydroxylase activity. Observed Km and Vmax values in the CYP2A6 reconstituted system were 1.48+/-0.37 microM and 3360+/-180 pmol product/min/nmol CYP, respectively.
Keywords: systém (enzymů) cytochromů P-450; Chromatography, High Pressure Liquid; jaterní mikrozomy; Spectrometry, Fluorescence; Sensitivity and Specificity; senzitivita a specificita; Microsomes, Liver; Humans; cytochrom P450 CYP2A6; aromatické hydroxylasy; Mixed Function Oxygenases; NADPH-cytochrom c-reduktasa; fluorescenční spektrometrie; Aryl Hydrocarbon Hydroxylases; hydroxylace; kumariny; Escherichia coli; krysa rodu Rattus; lidé; Hydroxylation; Recombinant Proteins; zvířata; NADPH-Ferrihemoprotein Reductase; Cytochrome P-450 Enzyme System; rekombinantní proteiny; oxygenasy se smíšenou funkcí; Kinetics; Coumarins; Cytochrome P-450 CYP2A6; Rats; Animals; vysokoúčinná kapalinová chromatografie; kinetika